BEST PRACTICES USED BY MALAYSIAN ENVIRONMENTAL WEBSITES: A COMPARISON STUDY - Abdullah, Aida Nasirah; Husin, Hanipah; Hasan, Hazmilah; Husain, Kalthom; Yahya, Aziz (Journal of Human Capital Development (JHCD), 2010)
This research is the first attempt to cover best practices for environmental websites in Malaysia. We chose five environmental NGOs in Malaysia (ENGOMs) for a case study, and evaluated website practices they used to communicate their missions and goals. A quantitative data was collected and analysed via content analysis of the five ENGOM websites. The content analysis of the websites sought to determine, identify and assess the best practices of the environmental websites features. The research questions focused on the use of online communication (OC) by ENGOMs in order to advocate specific environmental issues and potentially mobilise government or public action on these issues. How do the ENGOMs effectively use the website to communicate their organisations’ missions and goals? We conducted an extensive literature review to identify features of websites such as the usefulness of information, interactivity, navigability, and design that have been evaluated as important by previous researchers. Then we used these features as a basis for assessing the effectiveness of the practices of environmental websites in Malaysia. The web content analysis demonstrates that all the five ENGOMs had relatively small websites, providing useful information such as mission, goals, and organisation background. Most of the global issues advocated by them were meant to mobilise support and action. This is considered a rather ineffective use of OC. Interactivity features available across their websites were categorised at a ‘low’ level of utilisation. The ENGOMs did not fully utilise them for the purpose of conducting online campaigns and encouraging dialogue. The navigability of the five ENGOMs’ websites was categorised at a ‘good’ level, given that the majority of them provided good and easy navigation. The majority of the websites also met the ‘well designed’ requirements. Overall, the five ENGOMs have delivered most of the best practise features expected in effective environmental websites; Malaysian Nature Society (MNS) was ranked as the best website, while Sahabat Alam Malaysia (SAM) is at the opposite end of the spectrum. ENGOMs’ employees expressed views about enhancing their websites to be more interactive in the future. Financial constraints seemed to be the biggest problem faced by all ENGOMs in their endeavour to develop their websites. However, a key finding is that the websites with more resources did not use them as effectively as websites with fewer resources. Thus, one or two conscientious and well trained employees could be successful with limited resources. Keywords: online communication, interactivity, navigation, web design, online campaigns